Why fixed costs matter for proof-of-work based cryptocurrencies - Rod Garratt; Maarten R. C. van Oordt (Bank of Canada, 2020)
We assess how the cost structure of cryptocurrency mining affects the response of miners to exchange rate fluctuations and the immutability of cryptocurrency ledgers that rely on proof-of-work. We show that the amount of mining power supplied to currencies that rely on application-specific integrated circuits (ASICs), such as Bitcoin, responds less to adverse exchange rate shocks than other currencies respond to such shocks, a fact that is instrumental to avoiding double-spending attacks. The results may change if mining equipment used for one cryptocurrency can be transferred to another. For smaller currencies with low exchange rate correlation, transferability eliminates the protection that fixed costs provide. Our results weaken doomsday predictions for Bitcoin and other cryptocurrencies with declining block rewards.
Keywords: G10; L11; 330; Digital currencies and fintech; Payment clearing and settlement systems